Cytotoxic Flavokawain B Inhibits the Growth and Metastasis of Hepatocellular Carcinoma through UCK2 Modulation of the STAT3/Hif-1α/VEGF Signalling Pathway - Malami, Ibrahim; Alhassan, Alhassan M.; Adamu, Adamu Ahmed; Bello, Muhammad Bashir; Muhammad, Aliyu; Imam, Mustapha Umar (Current Drug Targets, 2023)
Background: Hepatocellular carcinoma (HCC) is associated with a high mortality rate due to early recurrence and its metastasis features. To this day, effective treatment options for metastatic HCC remain a major challenge to patient treatment. Flavokawain B (FKB) is a naturally occurring chalcone molecule capable of providing effective therapy against this life-threatening disease. Objective: This study investigated the anti-metastatic effects of FKB on the growth and development of metastatic HCC. Methods: HepG2 cells were used in this study and a neutral red assay was performed to determine the IC50value of FKB. Cell scratch and exclusion zone assays were performed to assess the rate of cell migration and invasion. Relative mRNA levels of UCK2, STAT3, VEGF and HIF-1α genes were quantified using RT-qPCR. Results: FKB inhibited the proliferation of HepG2 cells at an IC50 value of 28 μM after 72 h of incubation. Its cytotoxic effect was confirmed to induce apoptosis through the phase-contrast inverted microscope. Cell migration and invasion were significantly inhibited at 7, 14, and 28 μM of FKB as compared to untreated cells. The inhibition in the cell migration significantly increased with the increasing concentrations of the bioactive compound. The relative expression levels of the UCK2 gene and its downstream genes, STAT3, VEGF and HIF-1α, were significantly downregulated after 72 h exposure to FKB treatment. Conclusion: Our data suggest that FKB inhibited HepG2 proliferation and further suppressed its metastasis partly by regulating the STAT3/Hif-1α/VEGF signalling pathway. FKB could be a potential alternative and viable strategy against HCC.
Keywords: Flavokawain B